1998
DOI: 10.1002/(sici)1099-0488(199812)36:17<3035::aid-polb4>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of the nanovoid structure to the moisture absorption properties of epoxy resins

Abstract: Epoxy resins absorb significant quantities of moisture, typically 1 to 7% by weight for various formulations, which can greatly compromise their physical properties. It is known that polarity of the epoxy is a significant factor in determining the ultimate moisture uptake. However, the contribution from molecular topology still remains vague. In this work, the effects of molecular topology are elucidated by synthesizing novel epoxies where the polarity is maintained constant but the topology is systematically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
115
0
4

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 188 publications
(126 citation statements)
references
References 20 publications
7
115
0
4
Order By: Relevance
“…It has been shown that moisture can also cause structural damage by inducing microcavities or crazes in polymeric materials [33,34]. The formation of this structural damage can further accelerate water uptake [31,35], generate internal swelling stresses [8], or form chain scission via hydrolysis of ester bonds [4,29]. These irreversible water-resin interactions may be more pronounced when the polymers are allowed to undergo repeated sorption/desorption cycles [10] Using neat resin blends with known, and varying hydrophilicities to simulate non-solvented resin mixtures employed in various forms of commercial enamel and dentine adhesives, this study showed that water sorption and modulus reduction after water sorption are directly correlated with the polar attributes of the solubility parameters of these resins.…”
Section: Article In Pressmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that moisture can also cause structural damage by inducing microcavities or crazes in polymeric materials [33,34]. The formation of this structural damage can further accelerate water uptake [31,35], generate internal swelling stresses [8], or form chain scission via hydrolysis of ester bonds [4,29]. These irreversible water-resin interactions may be more pronounced when the polymers are allowed to undergo repeated sorption/desorption cycles [10] Using neat resin blends with known, and varying hydrophilicities to simulate non-solvented resin mixtures employed in various forms of commercial enamel and dentine adhesives, this study showed that water sorption and modulus reduction after water sorption are directly correlated with the polar attributes of the solubility parameters of these resins.…”
Section: Article In Pressmentioning
confidence: 99%
“…Because of small molecular size and high molar concentration of water, it can penetrate into nanometer-size free volume spaces between polymer chains [4,5], or cluster around functional groups that are capable of hydrogen bonding [6,7]. The major effect of water on polymer matrices is a depression of glasstransition temperature (T g ), that results in a decrease in thermal stability and polymer plasticization.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the molecular segments were more easily opened up by the bulky cycloaliphatic crosslinking joints, and the looser packing structure provided ease for water molecules to diffuse within the material and be adsorbed onto the polar sites. [32] In addition, the epoxy equivalent weight (EEW) and silicon content are the other two factors that should be taken into account for the interpretation of water absorption behavior of epoxy resins. An epoxide with lower EEW value would yield the higher content of polar groups when cured with anhydride, leading to an increased water absorption, whereas the incorporation of silicon element is advantageous for the improved water resistance.…”
Section: Water Absorption Propertiesmentioning
confidence: 99%
“…[5][6][7][8] Moisture transportation in polymers is related to molecular-sized holes (nanovoids) within the polymer matrix and to the polymer-water affinity. 1 In general, there are two states of water in the absorbed epoxy system.…”
Section: State Of Moisture Inside Of Molding Compoundmentioning
confidence: 99%